Art As Identity: Integrating Keris Blade Pattern Features Into Contemporary Abstract SculptureRE - Saiful Imaan Sharonee; Muhamad Khairi Shamsudin; Syed Zamzur Akasah Syed Ahmed Jalaluddin; Ahmad Fauzi Amir Hamzah (Badan Riset dan Inovasi Nasional (BRIN), 2025)
This practice-based research investigates how the symbolic features of Malay keris blade patterns can be reinterpreted in contemporary abstract sculpture. The study aims to explore traditional symbolism as a source of sculptural innovation and develop a method for translating intangible heritage into material form. Circularity, angularity, and ovality signifying hope, resilience, and protection were reimagined through three maquettes in wire and concrete. The process combined visual research, engagement with keris smiths, hermeneutic analysis, and iterative studio inquiry. The resulting forms layered helices, branching arcs, and planar folds evoke the stratified blade patterns (pamor) while establishing a new sculptural language. This research contributes: (1) a methodology for transforming cultural symbolism into contemporary form; (2) evidence of how abstraction sustains heritage narratives; and (3) adaptable design principles for public art and creative industries. The project positions the keris as a living cultural signifier and opens pathways for integrating Southeast Asian craft traditions into modern art and design.